2020
DOI: 10.4049/jimmunol.2000330
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA AW112010 Promotes the Differentiation of Inflammatory T Cells by Suppressing IL-10 Expression through Histone Demethylation

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to play important regulatory roles in gene expression, from histone modification to protein stability. However, the functions of most identified lncRNAs are not known. In this study, we investigated the role of an lncRNA called AW112010. The expression of AW112010 was significantly increased in CD4 + T cells from C57BL/6J mice activated in vivo with myelin oligodendrocyte glycoprotein, Staphylococcal enterotoxin B, or in vitro with anti-CD3 anti-CD28 mAbs, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) have been shown to play a critical role in gene expression, from histone modification to stability of proteins. Recent studies from our lab showed that an lncRNA called AW112010 was significantly induced in activated CD4+ T cells and CBD or THC could decrease the expression of AW112010 in T cells [ 101 ]. Additional studies showed that lncRNA AW112010 suppressed IL-10, thereby promoting the differentiation of inflammatory T cells through histone demethylation [ 101 ].…”
Section: Epigenetics Pathways Of Cannabinoid-mediated Suppression Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Long noncoding RNAs (lncRNAs) have been shown to play a critical role in gene expression, from histone modification to stability of proteins. Recent studies from our lab showed that an lncRNA called AW112010 was significantly induced in activated CD4+ T cells and CBD or THC could decrease the expression of AW112010 in T cells [ 101 ]. Additional studies showed that lncRNA AW112010 suppressed IL-10, thereby promoting the differentiation of inflammatory T cells through histone demethylation [ 101 ].…”
Section: Epigenetics Pathways Of Cannabinoid-mediated Suppression Of Inflammationmentioning
confidence: 99%
“…Recent studies from our lab showed that an lncRNA called AW112010 was significantly induced in activated CD4+ T cells and CBD or THC could decrease the expression of AW112010 in T cells [ 101 ]. Additional studies showed that lncRNA AW112010 suppressed IL-10, thereby promoting the differentiation of inflammatory T cells through histone demethylation [ 101 ]. Thus, cannabinoids could induce immunosuppressive cytokines such as IL-10 through downregulation of lncRNA AW112010.…”
Section: Epigenetics Pathways Of Cannabinoid-mediated Suppression Of Inflammationmentioning
confidence: 99%
“…AW112010, a top DE gene up-regulated in the airways upon re-challenge, was highly expressed in the airways of the re-challenged mouse (Figures 5B). AW112010 has also been reported capable of promoting the differentiation of inflammatory T cells 16 . Cbr2, a top DE gene down-regulated in the airways upon re-challenge, was highly expressed in the airways of the immunized mouse (Figures 5C), and may function in the metabolism of endogenous carbonyl compounds 17 and alveolar epithelial cell plasticity 18 .…”
Section: Biological Differences Upon K Pneumoniae Re-challengementioning
confidence: 99%
“…For example, after Toxoplasma gondii infection, non-shat022487 inhibits IL-12, tumor necrosis factor-α (TNF-α) and IFN-γ expression by downregulating the expression of the immune-activating molecule unc93b1 in human macrophages ( Liu et al, 2018 ), contributing to the establishment of chronic Toxoplasma infection. In staphylococcal enterotoxin B-activated CD4 + T cells of C57BL/6J mice, the long non-coding RNA (lncRNA) AW112010 inhibits IL-10 expression through histone demethylation and promotes the differentiation of inflammatory T cells ( Yang et al, 2020 ). During Mycobacterium tuberculosis infection, lncRNA-CD244 directly interacts with the polycomb repressive complexes(PRC2) subunit enhancer of zeste homolog 2(EZH2), which leads to histone H3 lysine (K) 27 methylation and confers a stronger inhibitory chromatin state at IFN-γ or TNF-α loci ( Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%